Efektifitas Akupresur terhadap Kelelahan dan Kecemasan Pasien Kanker - Malau, Mahda Chresginova; Novieastari, Enie; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the effectiveness of acupressure in treating fatigue and anxiety in cancer patients. The research method used is Systematic Review, through searching articles against six trusted databases, namely Cocharene, EbscoHost, ProQuest, Sage Journals, ScienceDirect, and Scopus, for article analysis using the PRISMA method. The results of the study showed that of the 10 research articles, there were articles which stated that acupressure was effective for overcoming fatigue and anxiety in cancer patients, but there were also articles which stated that acupressure had less significant effectiveness in overcoming fatigue and anxiety in cancer patients, especially when done with a small number of samples and during the chemotherapy process. In conclusion, acupressure has positive benefits in overcoming fatigue and anxiety, although in some cases the impact is not very significant. Acupressure is a therapy that does not use invasive procedures, is safe, cost-effective and easy to apply. Acupressure can be done independently by the patient by massaging the acupoints. Keywords: Acupressure, Anxiety, Cancer, Fatigue